High-Resolution Computed Tomography (HRCT) Chest Findings in Active Pulmonary Tuberculosis - Adhikari, Deepak; Raut, Yuvaraj; Poudel, Dipesh; Paudel, Bigyan; Bhatt, Manali; Adhikari, Shital (Nepalese Respiratory Journal, 2025)
Background: Tuberculosis (TB) is an airborne infection caused by the acid-fast bacillus Mycobacterium tuberculosis. It is estimated that about 10.8 million people fell ill with tuberculosis worldwide, and about 1.25 million of them died in 2023. In Nepal, nearly half of the population are estimated to harbor latent TB. Early diagnosis and effective treatment are the mainstay of the control of tuberculosis. Objective: This study aimed to evaluate the diagnostic utility of high-resolution computed tomography (HRCT) of the chest in detecting active pulmonary tuberculosis (PTB). Methods: It is a case-control study done in the Department of Radiodiagnosis at Chitwan Medical College, Teaching Hospital from August 2022 to January 2023. Adult patients with presumptive pulmonary TB who underwent both microbiological testing for Mycobacterium tuberculosis, and High-Resolution CT (HRCT) chest imaging were included. Patient’s demographics, clinical features, sputum microscopy for acid-fast bacilli (AFB), GeneXpert for MTB, and relevant HRCT chest findings were recorded in a predesigned proforma. Data were entered into Microsoft Excel and analyzed using IBM SPSS version 20.0. Results: Data from 72 patients with active pulmonary TB were analyzed. Of these, 46 patients (63.9%) had Mycobacterium tuberculosis identified via AFB staining, while the remaining 26 (36.1%) were diagnosed using GeneXpert. The control group included 35 sputum-negative cases where bacteria could not be isolated using GeneXpert. The mean age of patients was 56 years, and the majority were male (68.1%). The most frequent HRCT findings in active TB cases included tree-in-bud appearance (69.4%), enlarged mediastinal lymph nodes (65.3%), and consolidation (56.9%). The tree-in-bud pattern was significantly more common in TB-positive patients compared to controls. Conclusion: Common HRCT chest findings in pulmonary tuberculosis were tree-in-bud appearance, mediastinal lymphadenopathy, and consolidation. Tree-in-bud appearance in HRCT was significantly associated with bacteriologically confirmed pulmonary tuberculosis. When microbiological confirmation is delayed or negative, HRCT chest findings can support early initiation of treatment in suspected cases, thereby reducing community transmission and improving patient outcomes.